PEMANFAATAN MUSEUM SRI BADUGA SEBAGAI SUMBER PEMBELAJARAN SEJARAH DI SMA - Salsabila, Ardhita; Djono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the utilization of the Sri Baduga Museum as a resource for history education in high schools, covering the use of learning resources, the planning process, implementation, evaluation, and the challenges encountered. The research method employed is descriptive qualitative with a case study approach. Data collection techniques included observation, interviews, and document analysis. The results of the study indicate that the Sri Baduga Museum is utilized as a learning resource through out-of-classroom learning activities integrated with Hindu-Buddhist history curriculum in Indonesia, in accordance with the Learning Outcomes, and has been implemented systematically. Museum visits are able to create more contextual and meaningful learning, thereby increasing student engagement and developing critical thinking skills through direct observation of statues, inscriptions, and artifacts in the museum’s collection. However, their implementation still faces challenges such as limited time and managing student behavior during the activities. Therefore, more optimal strategies are needed so that the museum can be utilized sustainably as a source of history education.